PERHITUNGAN AWAL BULAN DAN KONVERSI DARI KALENDER MASEHI KE HIJRIAH PERSPEKTIF ILMU FALAK - Firawati, Firawati; Alimuddin , Alimuddin (Universitas Islam Negeri Alauddin Makassar, 2025)
Abstract Calculation of the beginning of the month and conversion of the Gregorian calendar to Hijri based on existing data. Calculating the beginning of the month is essentially calculating the position of the sun according to the established criteria. The position of the sun is not always the same every day. This research uses library research in the sense of looking for articles, theses, journals and books related to the author's title. The approach that the author uses is thesyar'I approach and the astronomical approach. According to the data source, research data is divided into two data, namely primary data and secondary data. The results of this study indicate that the perspective of astronomy on the calculation of the beginning of the month and the conversion of the Christian calendar to the Hijri used is the reckoning or calculation method. As for the month samples taken, namely Hisab at the beginning of Shawwal, Zulqaedah and Dzulhijjah 1444 H where istiqmal occurs, the number of days is made up to 30 days. Where the height of the new moon does not meet predetermined criteria. The conversion of the Gregorian calendar to the Hijri is used as a benchmark is the author's date of birth and the date of birth of the author's parents indicating that the calculation is in accordance with the method of astronomy, namely reckoning urfi. The implication of this research is that it is hoped that the government or religious leaders can broaden the horizons of those who already know or do not know about the procedure for calculating the beginning of the month and converting the Christian year to the Hijri year correctly and correctly in a modern way. It is hoped that students, especially the faculties of shari'ah and law and the department of astronomy, will be able to play an important and active role in providing knowledge to the public regarding the procedure for calculating the beginning of the month and converting the Christian year to the Hijri year.